Tapetum-Dependent Male Meiosis Progression in Plants: Increasing Evidence Emerges - Lei, Xiaoning; Liu, Bing (Frontiers in Plant Science, 2020)
In higher plants, male meiosis is a key process during microsporogenesis and is crucial for male fertility and seed set. Meiosis involves a highly dynamic organization of chromosomes and cytoskeleton and specifically takes place within sexual cells. However, studies in multiple plant species have suggested that a normal development of tapetum, the somatic cell layer surrounding the developing male meiocytes, is indispensable for the completion of male meiotic cell cycle. Disrupted tapetum development causes alteration in the expression of a large range of genes that are involved in male reproduction. Moreover, recent experiments suggest that small RNAs (sRNAs) present in the anthers, including microRNAs (miRNAs) and phased, secondary, small interfering RNAs (phasiRNAs), play a potential but important role in controlling male meiosis either by influencing the expression of meiotic genes in the meiocytes, or through other unclear mechanisms, supporting the hypothesis that male meiosis is non-cell autonomously regulated. In this mini-review, we summarize the recorded meiotic defects that occur in plants with defective tapetum development in both Arabidopsis and crops. Thereafter we outline the latest understanding on the molecular mechanisms that potentially underpin the tapetum-dependent regulation of male meiosis, and we especially discuss the regulatory role of sRNAs. In the end, we propose several outstanding questions that should be addressed in future studies.